Social determinants and cardiovascular care: A focus on vulnerable populations and the Jamaica experience - Madu, Ernest (FASEB Bioadv, 2021)
The concept of social determinants of health (SDOH) describes the complex interplay of social, economic, cultural, and environmental forces that influence health and illness and result in health inequities in society. In cardiovascular disease (CVD), SDOH play a significant role in contributing to the severe morbidity and mortality that various cardiovascular diseases inflict on our societies. The components of SDOH include wealth/income, employment status, education, social interactions/support, access to medical care (including mental health services), housing, transportation, physical environment (including availability of green space, water/sanitation, air pollution, noise pollution), work environment, access to good nutrition, social and community networks, access to technology and data, exposure to crime/social disorder/violence, exposure to adverse law enforcement/bad governance, and cultural norms. Leveraging reliable SDOH data is critical to addressing healthcare needs of the community. At‐risk populations must be connected to the appropriate resources needed to overcome these barriers to access to achieve better health outcomes. This review explores this theme with a focus on several vulnerable populations and offers possible strategies to reduce these inequalities. The Heart Institute of the Caribbean (HIC) was founded in 2005 to improve access to quality medical and cardiovascular services, made available to everyone regardless of their socioeconomic status. HIC has encountered and learned to navigate a myriad structural, institutional, socio‐economic, cultural, and behavioral barriers to appropriate CVD care for vulnerable populations in Jamaica and the wider Caribbean. The successes attained and the lessons learned by HIC can be replicated in other nations to address social determinants that impede cardiovascular and medical care in vulnerable populations and may alleviate the access gap in high‐quality care in developing countries and in underserved and marginalized communities in developed countries.